2022
DOI: 10.1155/2022/7373658
|View full text |Cite|
|
Sign up to set email alerts
|

The Drivers of the Behavioral Adoption Intention of BITCOIN Payment from the Perspective of Chinese Citizens

Abstract: The bitcoin payment innovation has gained wider interest around the world, but its adoption among the general population has been a challenge. Bitcoin as a peer-to-peer technology works with no central authority or banks, and the transaction management and issuing of bitcoin is carried out collectively by the network. One major debate on bitcoin development and diffusion is the critical matter of nongovernment intervention through adequate policy and regulatory framework and thus hinders people’s active partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 113 publications
(149 reference statements)
0
30
0
1
Order By: Relevance
“…The unified theory of acceptance and use of technology comprises eight different models [2,25,45] that facilitate comprehension of user-perceived technology adoption [2].…”
Section: Technology Acceptancementioning
confidence: 99%
See 1 more Smart Citation
“…The unified theory of acceptance and use of technology comprises eight different models [2,25,45] that facilitate comprehension of user-perceived technology adoption [2].…”
Section: Technology Acceptancementioning
confidence: 99%
“…Trust is a pivotal factor in the consumers' inclination to embrace technologies and services [22] as it aids in mitigating perceived risks and uncertainties associated with them, hence augmenting customers' levels of acceptance and intention to adopt [23,24]. Another critical component that must be considered before adopting innovative technologies is the acceptance of users [2,9,25,26]. Several models and frameworks have been established to elucidate the user adoption of innovative technologies, highlighting aspects that can influence user acceptance due to the significance of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that performance expectancy was the primary criterion which influence retailers' behavioral intention to adopt mobile payment apps [39]. The studies [40][41][42][43][44][45][46][47] have also studied the relationship between performance expectancy and behavioral intention. With this backdrop, the following hypotheses were formed: H1: there is no impact of performance expectancy on behavioural intention to use mobile payment applications.…”
Section: Introductionmentioning
confidence: 99%
“…In research conducted by Alshare and Lane [55], it was revealed that there is a strong relationship between effort expectancy and the behavioral intention of customers. The studies [40][41][42][43][44][45][46][47] have also evaluated the relationship between effort expectancy and behavioral intention. The above discussion led to the formulation of the following hypothesis: H2: there is no impact of effort expectancy on behavioral intention to use mobile payment applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation